Immune Responses Following Locoregional Treatment for Hepatocellular Carcinoma: Possible Roles of Adjuvant Immunotherapy - Ji-Won Han; Seung-Kew Yoon (MDPI AG, 2021)
Hepatocellular carcinoma (HCC) is a common cause of cancer-related deaths worldwide. Unlike other types of cancer, HCC can be treated with locoregional treatments (LRTs) such as radiofrequency ablation (RFA) or transarterial chemoembolization (TACE). However, recurrences following LRTs are common, and strategies to improve long-term outcomes need to be developed. The exhaustion of anti-tumor immunity in HCC has been well established in many reports and the immunomodulatory effects of LRTs (enhancement of tumor antigen-specific T cell responses after RFA, reduction of effector regulatory T cells after TACE) have also been reported in several previous studies. However, a comprehensive review of previous studies and the possible roles of immunotherapy following LRTs in HCC are not known. In this review, we discuss the immunological evidence of current clinical trials using LRTs and combined immunotherapies, and the possible role of this strategy.